2022
DOI: 10.3390/molecules27217405
|View full text |Cite
|
Sign up to set email alerts
|

Pectin: A Bioactive Food Polysaccharide with Cancer Preventive Potential

Abstract: Pectin is an acidic heteropolysaccharide found in the cell walls and the primary and middle lamella of land plants. To be authorized as a food additive, industrial pectins must meet strict guidelines set forth by the Food and Agricultural Organization and must contain at least 65% polygalacturonic acid to achieve the E440 level. Fruit pectin derived from oranges or apples is commonly used in the food industry to gel or thicken foods and to stabilize acid-based milk beverages. It is a naturally occurring compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 107 publications
1
13
0
Order By: Relevance
“…Pectin mainly produces reactive oxygen species to induce apoptosis, which is the opposite mechanism of action of APS [244]. Pectin is widely used as a gelling agent in jams and preserves by the food industry, whereas APS is mainly found in dietary supplements and traditional medicine [23,245].…”
Section: Astragalus Polysaccharide and Pectin Polysaccharidementioning
confidence: 99%
See 1 more Smart Citation
“…Pectin mainly produces reactive oxygen species to induce apoptosis, which is the opposite mechanism of action of APS [244]. Pectin is widely used as a gelling agent in jams and preserves by the food industry, whereas APS is mainly found in dietary supplements and traditional medicine [23,245].…”
Section: Astragalus Polysaccharide and Pectin Polysaccharidementioning
confidence: 99%
“…In addition to their benefits as soluble dietary fibers, modified pectins, particularly modified citrus pectins, have beneficial effects on the development and spread of malignant tumors, including colon and breast cancer [245]. Pectin-derived chemicals slow cell development and promote apoptosis [246].…”
Section: Astragalus Polysaccharide and Pectin Polysaccharidementioning
confidence: 99%
“…Pectin may also help prevent the reabsorption of bile salt micelles, although the exact mechanism is not fully understood [146,147]. Studies have found that pectin and its derivatives may suppress cancer cell growth and stimulate apoptosis [148,149]. When combined with other plant compounds, pectin has demonstrated the ability to decrease the invasive potential of human breast cancer cells.…”
Section: Digestive Fibermentioning
confidence: 99%
“…Pectin has the ability to detect Gal-3 components, which is one of the major mechanisms governing cancer growth and metastasis. Citrus pectin was employed to target Gal3, which successfully inhibited metastatic growth …”
Section: Application Of Pectinmentioning
confidence: 99%
“…Citrus pectin was employed to target Gal3, which successfully inhibited metastatic growth. 95 4.3. Pectin as a Rheology Modifier.…”
Section: Application Of Pectinmentioning
confidence: 99%